LAYANAN SMS BANKING DAN INTERNET BANKING BANK SYAIRAH UNTUK MENINGKATKAN CUSTOMER EXPERIENCE - Purnomo Purnomo; Risma; Ramayani Yusuf (POLITEKNIK PIKSI GANESHA, 2020)
Abstract This research aims to identify the influence or impact of banking digitization, namely SMS Banking and Internet Banking services on the customer experience at Bank BJ Syariah Bandung. The survey was tested on 111 BJB Bank customers who have sms banking and internet banking (mobil-e mashlahat) in their software. Customers regularly carry out transactions using sms banking or internet banking. The method of this study, namely quantitative and information for this research, was collected through a questionnaire. This research uses a multiple linear regression equation model to evaluate the suitability of a theoretical model that is being analyzed in terms of empirical information, as well as to test the significance of the hypothesis. The research results show that SMS banking affects customer experience while internet banking does not affect partial customer experience. Simultaneously, SMS banking and internet banking affect customer experience by 28.1%, on the contrary 71.9% are influenced by other aspects that were not examined in this research.